Developing a Model for Teaching Speaking Skills Based on Cooperative and Contextual Learning - Al Ghozali, M. Dzikrul Hakim; ., Mustamim; Bahrudin, Uril; ., Syuhadak (JURNAL IJ-ATL, 2023)
Teaching Arabic speaking skills to non-native learners is a fundamental component in fostering communicative competence and intercultural interaction, especially within Islamic education institutions. This study explores the development of a teaching model that combines cooperative learning strategies with contextual approaches to enhance beginner-level speaking proficiency. The research was conducted at Universitas KH. Abdul Wahab Hasbullah using a qualitative-descriptive method, with data gathered through classroom observation, interviews with lecturers and students, as well as documentation of instructional materials and speaking tasks. The findings indicate that the integration of cooperative learning through peer collaboration, role-plays, and group discussions and contextual scenarios such as market simulations and daily life dialogues creates a dynamic, learner-centered environment that encourages active language use and reduces performance anxiety. This model promotes spontaneous interaction, vocabulary development, and strategic language use while fostering learner autonomy and confidence. The study concludes that a cooperative-contextual model is not only pedagogically sound but also practically applicable, especially for institutions seeking low-cost, high-impact solutions for Arabic speaking instruction. The implications support the implementation of adaptive, engaging, and authentic speaking practices to optimize student outcomes in Arabic language learning.